Reimagining hospital management: the balanced scorecard as a catalyst for employee retention and organizational excellence - Feng Guo; Ying Sophie Huang; Moeki Nemoto; Moeki Nemoto (Frontiers in Public Health)
Employee turnover in healthcare institutions is a critical issue affecting both quality of care and organizational costs. This study examines the potential impact of the Balanced Scorecard (BSC) as a communication tool on employee turnover rates in a Japanese hospital setting. A case study of Bethlehem Garden Hospital in Tokyo, Japan, was conducted to examine turnover rates before and after the implementation of BSC. The study also compares these rates to industry averages in Japan and the United States. The results show a significant reduction in turnover rates from 23.6% in 2015 to 3.4% in 2023 following the implementation of BSC, which is lower than both national and international industry averages. This reduction corresponded with increased employee engagement scores. The study suggests that the BSC when effectively implemented and communicated, can help reduce turnover by improving organizational alignment, employee engagement, and trust. Although the single case study design limits generalizability, these findings provide valuable insights into the potential of BSC as a strategic tool for addressing turnover in healthcare settings. Future research directions are suggested to validate these findings further in diverse healthcare environments.